2011
DOI: 10.4103/0974-2700.83861
|View full text |Cite
|
Sign up to set email alerts
|

Neurological outcomes of neurosurgical operations for multiple trauma elderly patients in Hong Kong

Abstract: Background:We aimed to investigate neurological outcomes in elderly patients with multiple trauma, and to review their clinical outcomes following neurosurgical operations.Patients and Methods:The study was conducted in a regional trauma center in Hong Kong. We collected prospective data on consecutive trauma patients from January 2001 to December 2008. Patients with multiple trauma (as defined by Injury Severity Score of 15 or more), with both head injury and extracranial injury, were included for analysis.Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 18 publications
2
2
0
Order By: Relevance
“…In addition, it should be noted that in this study most of the people affected by accidents had recovered and only a small number of accident victims had died, which is consistent with the final accident outcomes as determined in previous studies conducted on the age group of individuals 60 years old and older (37,38). Although most injuries end in recovery, each of these injuries can cause significant mental, physical, and economic and financial difficulties for individuals and societies (37,38).…”
Section: Discussionsupporting
confidence: 90%
“…In addition, it should be noted that in this study most of the people affected by accidents had recovered and only a small number of accident victims had died, which is consistent with the final accident outcomes as determined in previous studies conducted on the age group of individuals 60 years old and older (37,38). Although most injuries end in recovery, each of these injuries can cause significant mental, physical, and economic and financial difficulties for individuals and societies (37,38).…”
Section: Discussionsupporting
confidence: 90%
“…Further associations demonstrate the increased likelihood of severe extracranial injury with RTA and falls. Paralleling these findings previous studies showed clinical outcomes worsen with increasing age [ 26 , 27 , 28 ] with low energy falls being four times as common mechanism over the age of 65 [ 28 ]. There is emerging relevance of TBI in the elderly population due to its increasing incidence, which is one of the key features of changing epidemiology in traumatic brain injury [ 1 ].…”
Section: Discussionsupporting
confidence: 82%
“…Mortality in elderly patients suffering major trauma is much higher than that in their younger counterparts, 22 23 but with appropriately configured services good outcomes can be achieved. 3 24 25 For many elderly patients suffering trauma undergoing non-operative management, targeted rehabilitation on a dedicated trauma unit may yield similar mortality benefits to those observed in orthopaedic trauma units with embedded orthogeriatric services. 26 Identification and early aggressive management of patients at higher risk of developing complications such as those with blunt chest wall trauma 27 may improve mortality and morbidity while reducing hospital stay.…”
Section: Discussionmentioning
confidence: 99%